Wachstum bei Störungen und Normvarianten der Pubertät - Binder, Gerhard; Bettendorf, Markus (Monatsschrift Kinderheilkunde, 2019)
BackgroundDisorders of puberty may affect growth.ObjectiveHow do precocious puberty, constitutional delay of growth and puberty (CDGP) and hypogonadism impact parameters of growth, such as growth velocity, bone maturation and adult height and when is treatment required?Material and methodsThis article is based on the results of a working party meeting of pediatric endocrinologists. Each author carried out a review of the current literature about growth in the context of disorders of pubertal development and the respective treatment.ResultsIf untreated precocious puberty almost always results in short stature in adulthood. Affected children can achieve an individual adult target height if treatment with gonadotropin-releasing hormone (GnRH) analogues is started early. The CDGP is a slow variant of childhood growth rate with normal unaffected adult height and treatment is not necessary. Overweight can be associated with an acceleration of growth and pubertal maturity but adult height is also unaffected. Children with hypogonadism usually reach normal adult height after pharmaceutical induction of puberty. Complex hypothalamic and hypopituitary disorders (hypogonadism plus deficiency of growth hormones), e.g. that can occur after cancer treatment in childhood, need early diagnosis and individualized therapy to preserve the growth potential of the patient.ConclusionEarly diagnosis and adequate therapy of disorders of puberty are the cornerstones for an optimal growth outcome of affected children.
Online publiziert: 6. November 2017
Gesehen am 29.04.2019